Factors Associated With False-Negative Endoscopic Biopsy Results After Neoadjuvant Chemoradiotherapy in Patients With Esophageal Squamous Cell Carcinoma. Issue 8 (February 2015) - Chao, Yin-Kai; Yeh, Chi-Ju; Lee, Mu-Hsien; Wen, Yu-Wen; Chang, Hsien-Kun; Tseng, Chen-Kan; Liu, Yun-Hen
Abstract : Abstract: The usefulness of endoscopic biopsy following neoadjuvant chemoradiotherapy (nCRT) is limited because of its high false-negative (FN) rates. However, data on the factors associated with FN biopsy results remain scarce. The purpose of this study was to investigate factors associated with FN results on endoscopic biopsies in patients with esophageal squamous cell carcinoma (ESCC) following nCRT. We retrospectively reviewed the records of ESCC patients who were treated at the Chang Gung Memorial Hospital, Taoyuan, Taiwan, between 1999 and 2013. Inclusion criteria were receiving nCRT as first-line treatment before esophagectomy and having been preoperatively submitted to an endoscopic biopsy. Endoscopic findings at the lesion site were classified into 6 distinct categories: stricture, tumor, ulcer, scar, other findings, or normal. Univariate and multivariate analyses were used to identify factors associated with FN biopsy findings. A total of 227 patients were selected, of which 92 (41.9%) had positive biopsy results. Among patients with negative biopsy findings (n = 135), 85 were found to have residual cancer on the resected esophagus. Multivariate analysis identified endoscopic findings as the only independent predictor of FN biopsy results. The negative predictive values were 77.8%, 61.9%, 52.6%, 30.3%, 23.1%, and 20.0% for the normal, scar, other findings, ulcer, stricture, and tumor categories, respectively ( P  < 0.001). In ESCC patients, the FN rate of endoscopic biopsy after nCRT is associated with the type of residual lesion.